Tofacitinib Versus Non-Tumor Necrosis Factor Biologics for Patients With Active Rheumatoid Arthritis - Yukio NAKAMURA; Takako SUZUKI; Hideshi YAMAZAKI; Hiroyuki KATO (Archives of Rheumatology, 2018)
Objectives: This study aims to compare the disease status of patients with active rheumatoid arthritis (RA) after treatment with tofacitinib or non- tumor necrosis factor (TNF) biologics. Patients and methods: The study included a total of 50 RA patients (18 males, 32 females; mean age 68.3±1.3 years; range 42 to 92 years). We prospectively and randomly enrolled 25 patients for treatment with tofacitinib (Tofa group: 10 males, 15 females; mean age 68.3±2.0 years; range, 42 to 92 years) and 25 for treatment with non-TNF biologics (non-TNF group: 8 males, 17 females; mean age 68.3±1.7 years; range 51 to 92 years). Mean disease activity score 28 (DAS28), C-reactive protein (CRP), clinical disease activity index (CDAI), health assessment questionnaire (HAQ)-disability index (DI), and matrix metalloproteinase-3 values were recorded at baseline and at 4, 8, and 12 months. Results: There was a significant difference in the percent changes of DAS28, CRP and CDAI at every time point versus baseline in both treatment groups. HAQ-DI was also significantly different at every time point in both groups except for at four months in the non-TNF group. Conclusion: Tofacitinib was well tolerated in active RA patients and exerted effects comparable to those of non-TNF biologics.